Facile one pot synthesis of nitrogen doped reduced graphene oxide supported Co3O4 nanoparticles as bifunctional catalysts for the reduction of 4-nitrophenol and NaBH4 hydrolysis. (22nd March 2023) - Jacob, Bibin; Mohan, Manoj; K C, Dhanyaprabha; Thomas, Hysen
Abstract: The development of catalyst materials with significant potential and multifunctional applicability is essential for sustainable energy and environmental applications. The present work reports the preparation of nitrogen doped reduced graphene oxide supported Co3 O4 nanoparticles (NGCO) via a simple and cost effective one pot synthesis method, at a relatively low temperature. The prepared NGCO composites were employed for the first time as active bifunctional catalysts in the reduction of 4-nitrophenol (4NP) and NaBH4 hydrolysis. The NGCO catalyst exhibited excellent catalytic activity and stability for the 4NP conversion with a mass normalized rate constant of 97.8 min −1 g −1 at 303 K. The concentration (0.7 mM) and volume (20 mL) of the 4NP solution used in this study was higher than most of the works in the literature and that signifies the novelty of the prepared NGCO catalyst materials. The NGCO catalysts also showed potential activity and durability in liberating hydrogen from NaBH4, via hydrolysis, with a maximum specific hydrogen generation rate of 2090.6 mL min −1 gCo −1 . The kinetics of the catalytic NaBH4 hydrolysis reaction was investigated using zero order and first order kinetic models. The experimental data was well-described with the zero-order kinetic model. The improved catalytic activity of the NGCO composites relative to the unsupported Co3 O4 nanoparticles is due to the excellent dispersibility of the active sites and the synergetic action of both Co3 O4 and N doped graphene support in NGCO. Graphical abstract: Image 1 Highlights: Nitrogen doped graphene supported Co3 O4 (NGCO) composites were prepared through a simple one pot synthesis route. The NGCO composites exhibited excellent catalytic activity in 4-Nitrophenol (4NP) reduction and NaBH4 hydrolysis. The introduction of nitrogen doped reduced graphene oxide support enhanced the catalytic performance of NGCO. The NGCO catalysts displayed good stability and reusability in both 4NP reduction and NaBH4 hydrolysis reactions.